Comprative study of ecodynamic of halogenated micropollutant of historical and emergent interest in the Seine estuary - Gallien, Marine (CCSD, 2021)
In a context of global change, the effects of anthropogenic pollution are significant. This pollution is linked to urbanization, industrial activity and intensive agriculture. These multiple sources generate many categories of pollution, including chemical pollution. In order to better understand the ecodynamics of certain ubiquitous, toxic and bioaccumulative pollutants, the Seine estuary was chosen because it is the final receptacle of a watershed subject to strong anthropic pressure. Several compartments were studied there. Four species of seabirds (European herring gull: Larus argentatus; lesser black-backed gull: Larus fuscus; great black-backed gull: Larus marinus; European shag : Phalacrocorax aristotelis) sentinels, bioindicators, representative of a high trophic level and having varied feeding habits characteristic of estuarine environments were chosen in order to follow their impregnation in different classes of historical contaminants such as polychlorinated biphenyls (PCBs), organochlorinated pesticides (OCPs) and polybrominated diphenyl ethers (PBDEs) and contaminants of more emerging interest such as per- and poly-fluoroalkyl compounds (PFAS). PCBs, hexabromocyclododecane (HBCDD) and PFAS were also monitored in the environment and food web of common sole (Solea solea) in order to understand the transfers from sediment to biota, within the benthic food web, but also between the juvenile stages of an organism of major halieutic and ecological interest. Dans un contexte de changement global, les effets de la pollution d'origine anthropique sont importants. Cette pollution est liée à l'urbanisation, l'activité industrielle ou encore l'agriculture intensive. Ces multiples sources génèrent de nombreuses catégories de pollution, dont la pollution chimique. Afin de mieux comprendre l'écodynamique de certains polluants ubiquistes, toxiques et bioaccumulables, l'estuaire de Seine a été choisi car il constitue le réceptacle final d'un bassin versant soumis à une forte pression anthropique. Plusieurs ...